2011
DOI: 10.1029/2010jd015579
|View full text |Cite
|
Sign up to set email alerts
|

Does a dipole mode really exist in the South Atlantic Ocean?

Abstract: [1] This study investigates the existence of a dipole mode in the sea surface temperatures (SST) over the South Atlantic Ocean (SAO), using observational and reanalysis data sets from 1950 to 2008. Our results demonstrate that an opposite SST mode, the SAO dipole (SAOD) occurs in the SAO as the anomalous surface waters in the northeastern part; that is, the Atlantic Niño sector and the southwestern part off the Argentina-UruguayBrazil coast are consistently anticorrelated in all months. A typical SAOD episode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 44 publications
8
79
1
4
Order By: Relevance
“…This mode has a structure similar to the South Atlantic Ocean Dipole (SAOD) described by Nnamchi et al (2011), both in its boreal summer configuration ( Figure 1a) and its seasonal evolution (not shown).…”
Section: Decadal Differences In the Equatorial Modementioning
confidence: 90%
See 3 more Smart Citations
“…This mode has a structure similar to the South Atlantic Ocean Dipole (SAOD) described by Nnamchi et al (2011), both in its boreal summer configuration ( Figure 1a) and its seasonal evolution (not shown).…”
Section: Decadal Differences In the Equatorial Modementioning
confidence: 90%
“…This mode is similar to the one that Rodriguez-Fonseca et al The question about the opportunity of referring to these two patterns as the Equatorial Mode can be controversial. In this way, Nnamchi et al (2011) argue that the SAOD and the EM are different modes of variability in which different dynamics operate, especially in the subtropical South Atlantic. Nevertheless, we have obtained the two patterns only by looking at the Atlantic variability over the equatorial region, and they also appear as the first mode of variability in the tropical Atlantic for each of the sub-periods of the study (not shown), as well as the SST pattern of the first modes of co-variability between tropical Atlantic SST and summer Mediterranean precipitation computed before and after the 1970's (Losada et al, 2012b).…”
Section: Decadal Differences In the Equatorial Modementioning
confidence: 99%
See 2 more Smart Citations
“…1 displays the strongest decadal change over the region (25°-50°S, 50°-10°W), which is a little bit north to the box used in Latif et al (2006). Thus, to better characterize the decadal change in South Atlantic, we define the SAMV index over the region (25°-50°S, 50°-10°W) in southwest South Atlantic, similar to the location of southwest pole of the interannual South Atlantic Ocean dipole (SAOD) (Morioka et al 2011;Nnamchi et al 2011). Because the SAMV indices defined based on datasets ERSSTv4 and HadISST2.1 are highly correlated (r = 0.92, significant at the 99% confidence level), so we will only show the results based on dataset ERSSTv4 in the remainder of this paper unless otherwise stated.…”
Section: Thermodynamic Equationmentioning
confidence: 99%